Reinforced recycled polyethylene and high-density polyethylene composite material and preparation method thereof
By adding KH550-treated glass fiber and eggshell powder to the recycling polyethylene and high-density polyethylene composite material and performing specific treatment, the problem of reduced performance in the recycling process is solved, and the composite material is excellent Mechanical properties and good thermal stability.
Patent Information
- Application Number
- CN202411613471.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
Recycling of polyethylene requires multiple physical and chemical treatments during the recycling process, resulting in reduced toughness, stiffness, strength and heat resistance, and the effective interface combination of fiber reinforced composite materials is difficult to achieve, resulting in reduced plasticity or toughness.
Recycled polyethylene, high-density polyethylene, polyethylene grafted maleic anhydride, glass fiber treated with KH550 and eggshell powder treated with KH550 are melted by thorough mixing and melting within a specific temperature range. Extrusion and granulation to prepare composite materials with excellent mechanical properties and good thermal stability.
The crystallinity, storage modulus, tensile strength, bending strength and impact strength of composite materials have been improved. The Vica softening temperature and 5% weight loss temperature have also been significantly improved, solving the problem of reduced performance of recovered polyethylene during recycling, providing A new approach is made to recycle thermoplastic resin modification and design of high-performance composite materials.
Smart Images

Figure CN119463334A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, and in particular to a reinforced recycled polyethylene and high-density polyethylene composite material and a preparation method thereof. Background Art
[0002] In recent years, polymer composites have played a vital role in many fields such as construction, automobiles, ships, aerospace, etc. Among them, thermoplastic materials are easy to process and recyclable, and their production and utilization have maintained a strong growth momentum in the composite materials market. Polyethylene (PE) is the most widely produced thermoplastic resin in the world, among which high-density polyethylene (HDPE) has excellent acid resistance, alkali resistance, organic solvent resistance, and excellent electrical insulation properties. Therefore, it is widely used in various industries such as automobile manufacturing, agriculture, packaging, construction and pharmaceuticals.
[0003] The huge output of polyethylene waste plastic products will have a significant negative impact on soil, water quality, animals and plants, so it is urgent to recycle polyethylene to reduce white pollution. In addition, recycled polyethylene needs to undergo multiple physical and chemical treatments during the recycling process, which will seriously affect the toughness, stiffness, strength and heat resistance of polyethylene. In recent years, the development and utilization of fiber-reinforced polyethylene composites have made great progress. However, the effective interface bonding between different materials is crucial for fiber-reinforced composites. The reinforcement of composites usually leads to reduced plasticity or toughness. Therefore, it is necessary to design a reinforced recycled polyethylene and high-density polyethylene composite material and a preparation method to solve the above problems. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the problems existing in the existing reinforced recycled polyethylene and high-density polyethylene composite material and preparation method, the present invention is proposed.
[0006] Therefore, the object of the present invention is to provide a reinforced recycled polyethylene and high-density polyethylene composite material and a preparation method, which is suitable for solving the problem that recycled polyethylene needs to undergo multiple physical and chemical treatments during the recycling process, which will seriously affect the toughness, stiffness, strength and heat resistance of the polyethylene. The reinforcement of the composite material will also lead to a decrease in plasticity or toughness.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a reinforced recycled polyethylene and high-density polyethylene composite material, the composite material comprising:
[0008] Recycled polyethylene, high-density polyethylene, polyethylene grafted with maleic anhydride, glass fiber treated with KH550, and eggshell powder treated with KH550 after constant temperature drying;
[0009] Among them, the mass proportion of recycled polyethylene is 32.25%;
[0010] High-density polyethylene accounts for 32.25% by mass;
[0011] A certain proportion of polyethylene grafted with maleic anhydride, glass fiber treated with KH550, and eggshell powder treated with KH550;
[0012] The recycled polyethylene, high-density polyethylene, polyethylene grafted with maleic anhydride, glass fiber treated with KH550 and eggshell powder treated with KH550 are fully mixed, and the mixed materials are melted, extruded and granulated to obtain the composite material.
[0013] As a preferred scheme of the reinforced recycled polyethylene and high-density polyethylene composite material described in the present invention, the glass fiber treated with KH550 refers to glass fiber treated with a KH550 mixed solution with a mass concentration of 1.0%, and the eggshell powder treated with KH550 refers to eggshell powder treated with a KH550 mixed solution with a mass concentration of 1.0%.
[0014] As a preferred solution of the reinforced recycled polyethylene and high-density polyethylene composite material described in the present invention, the KH550 mixed solution with a mass concentration of 1.0% is prepared by adding silane coupling agent KH550 to a solution with a mass ratio of distilled water to ethanol of 1:1.
[0015] As a preferred solution of the reinforced recycled polyethylene and high-density polyethylene composite material of the present invention, the constant temperature is 80° C. and the drying time is 8 hours.
[0016] As a preferred embodiment of the reinforced recycled polyethylene and high-density polyethylene composite material described in the present invention, the recycled polyethylene, high-density polyethylene, polyethylene grafted with maleic anhydride, glass fiber treated with KH550 and eggshell powder treated with KH550 are melted, extruded and granulated within a temperature range of 175°C to 180°C, and the produced granules are dried at 80°C for 8 hours.
[0017] As a preferred solution of the reinforced recycled polyethylene and high-density polyethylene composite material described in the present invention, the mass proportion of the polyethylene grafted with maleic anhydride is 5%, and the glass fiber is modified with silane coupling agent KH550 to enhance the compatibility of the glass fiber with recycled polyethylene / high-density polyethylene.
[0018] As a preferred solution of the reinforced recycled polyethylene and high-density polyethylene composite material described in the present invention, the mass proportions of the glass fiber treated with KH550 and the eggshell powder treated with KH550 are 30% and 0.5% respectively, so that a strong crystal network structure is formed inside the material, the crystallinity of the composite material is enhanced, and thus the heat resistance is enhanced.
[0019] As a preferred embodiment of the reinforced recycled polyethylene and high-density polyethylene composite material of the present invention, the addition of 30% of glass fiber treated with KH550 and 0.5% of eggshell powder treated with KH550 enhances the loss modulus and storage modulus of the composite material.
[0020] As a preferred solution of the reinforced recycled polyethylene and high-density polyethylene composite material described in the present invention, KH550 with a mass concentration of 1.0% enhances the interfacial adhesion between the eggshell powder and the matrix, increases the roughness and viscosity inside and on the surface of the composite material, complicates the heat transfer path of the material during the melting process, and improves the heat resistance of the composite material.
[0021] A method for preparing a composite material of reinforced recycled polyethylene and high-density polyethylene, the preparation method is applicable to any of the above composite materials, and the preparation method comprises the following steps:
[0022] S1: Material drying: Recycled polyethylene, high-density polyethylene, glass fiber treated with KH550, polyethylene grafted with maleic anhydride and eggshell powder treated with KH550 were dried at a constant temperature of 80°C for 8 hours;
[0023] S2: adding silane coupling agent KH550 to a solution with a mass ratio of distilled water to ethanol of 1:1 to prepare a mixed solution with a mass concentration of 1.0% KH550, and after ultrasonic treatment of the mixed solution for 1 hour, the dried glass fiber and eggshell powder were respectively immersed in an appropriate amount of the mixed solution for 2 hours, and then the treated materials were transferred to an oven at 80°C for 4 hours;
[0024] S3: The components of the composite material are fully mixed, and the uniformly mixed materials are melted, extruded and granulated at a temperature range of 175° C. to 180° C., and the granules are dried at 80° C. for 8 hours.
[0025] Beneficial effects of the present invention: The present invention uses recycled polyethylene / high-density polyethylene (R-PE / HDPE) as a matrix, polyethylene grafted maleic anhydride (PE-g-MAH) as a compatibilizer, glass fiber (GFKH) treated with silane coupling agent KH550 and eggshell powder (ESPKH) as reinforcing phases to prepare a new composite material with excellent mechanical properties, good thermal stability and crystallization properties. The results show that after adding 30wt% GFKH and 0.5wt% ESPKH, the composite material (GFKH / ESPKH0.5) The crystallinity, storage modulus, tensile strength, flexural strength and impact strength are increased by 33.3%, 107.9%, 125.3%, 115.3% and 79.8% compared with R-PE / HDPE, respectively. Thermal analysis shows that the Vicat softening temperature (VST) and 5% weight loss temperature (T5%) are increased by 6.9°C and 41°C, respectively, which provides a new approach for the modification of recycled thermoplastic resins and the design of high-performance composites. GFKH / ESPKH0.5 composites have great potential in the application of sustainable building components, parts and products. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:
[0027] Figure 1 A schematic diagram of a process for preparing a composite material of enhanced recycled polyethylene and high-density polyethylene proposed by the present invention;
[0028] Figure 2 It is a schematic diagram of the second embodiment of the present invention;
[0029] Figure 3 This is a schematic diagram of Embodiment 3 of the present invention;
[0030] Figure 4 is a schematic diagram of a fourth embodiment of the present invention;
[0031] Figure 5 is a schematic diagram of Embodiment 5 of the present invention;
[0032] Figure 6 is a schematic diagram of Embodiment 6 of the present invention;
[0033] Figure 7 A schematic diagram of a seventh embodiment of the present invention;
[0034] Figure 8 is a schematic diagram of Embodiment 8 of the present invention;
[0035] Fig. 9 is a schematic diagram of Embodiment 9 of the present invention;
[0036] Fig.10 This is a schematic diagram of the steps of a method for preparing a reinforced recycled polyethylene and high-density polyethylene composite material proposed by the present invention. DETAILED DESCRIPTION
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.
[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0040] Secondly, the present invention is described in detail with reference to the schematic diagram. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.
[0041] Embodiment 1
[0042] Reference Figure 1 and Fig.10 , as one embodiment of the present invention, provides a reinforced recycled polyethylene and high-density polyethylene composite material, the composite material comprising:
[0043] R-PE (recycled polyethylene), HDPE (high-density polyethylene), PE-g-MAH (polyethylene grafted with maleic anhydride), GFKH (glass fiber treated with KH550) and ESPKH (eggshell powder treated with KH550) after constant temperature drying, the constant temperature is 80℃, and the drying time is 8h;
[0044] Among them, the mass proportion of R-PE is 32.25%;
[0045] The mass percentage of HDPE is 32.25%;
[0046] The mass proportion of PE-g-MAH is 5%;
[0047] GFKH accounts for 30% by mass;
[0048] The mass share of ESPKH is 0.5%;
[0049] The KH550 mixed solution with a mass concentration of 1.0% is prepared by adding silane coupling agent KH550 to a solution with a mass ratio of distilled water to ethanol of 1:1, GFKH refers to glass fiber treated with the KH550 mixed solution with a mass concentration of 1.0%, and ESPKH refers to eggshell powder treated with the KH550 mixed solution with a mass concentration of 1.0%;
[0050] The R-PE, HDPE, PE-g-MAH, GFKH and ESPKH are fully mixed, and the mixed materials are melted, extruded and granulated;
[0051] The mixture of R-PE, HDPE, PE-g-MAH, GFKH and ESPKH was melted, extruded and granulated at a temperature range of 175°C to 180°C, and the granules were dried at 80°C for 8 hours.
[0052] In order to facilitate the filling of experimental data, the English annotations of the corresponding components are as follows: recycled polyethylene is R-PE, high-density polyethylene is HDPE, polyethylene grafted with maleic anhydride is PE-g-MAH, glass fiber treated with KH550 is GFKH, eggshell powder treated with KH550 is ESPKH, and glass fiber is GF;
[0053] Table 1: R-PE / HDPE and its composite material formula
[0054]
[0055]
[0056] A method for preparing a composite material of reinforced recycled polyethylene and high-density polyethylene, the preparation method is applicable to any of the above composite materials, and the preparation method comprises the following steps:
[0057] S1: Material drying: R-PE, HDPE, GFKH, PE-g-MAH and ESPKH were dried at a constant temperature of 80 °C for 8 h;
[0058] S2: Silane coupling agent KH550 was added to a solution with a mass ratio of distilled water to ethanol of 1:1 to prepare a mixed solution with a mass concentration of 1.0% KH550. After the mixed solution was ultrasonically treated for 1 hour, the dried GF and ESP were immersed in an appropriate amount of the mixed solution for 2 hours respectively. Subsequently, the treated materials were transferred to an oven at 80°C for 4 hours.
[0059] S3: The components of the composite material are fully mixed, and the uniformly mixed materials are melted, extruded and granulated at a temperature range of 175° C. to 180° C., and the granules are dried at 80° C. for 8 hours.
[0060] Embodiment 2
[0061] Reference Figure 2 , which is an embodiment of the present invention, is measured using a Fourier transform infrared spectrometer (FTIR) (ThermoScientific Nicolet IS20) at 400-4000cm -1 Chemical analysis of GF, GFKH, ESP and ESPKH was performed within a wavenumber range of 1.
[0062] Infrared (FTIR) spectra of GF and ESP and scanning electron microscope (SEM) analysis of ESP:
[0063] exist Figure 2 In the figure, (a) infrared spectra (FTIR) curves of GF and GFKH;
[0064] (b) FTIR curves of ESP and ESPKH;
[0065] (c) Mapping image of ESPKH;
[0066] (d) Scanning electron microscope (SEM) image of ESPKH0.5.
[0067] In order to verify the effective combination of KH550 with GF and ESP, and to study the distribution of ESPKH in the R-PE / HDPE matrix, we conducted infrared analysis and observed the dispersion of ESPKH by scanning electron microscopy. Figure 2 (a) and (b) are the infrared spectral images before and after GF and ESP preprocessing, respectively. The mapping image of ESPKH is shown in Figure 2 (c) shows the SEM image of ESPKH0.5. Figure 2 (d) Figure 2 (a) at 774 cm -1 and 1020cm -1The peaks at 750-1050 cm-1 are related to the bending vibration and stretching vibration of Si-O, which are the main chemical characteristics of GF. -1 The shape of the absorption peak at 1590 cm-1 changed significantly, indicating that many Si-O-Si bonds were formed. -1 and 3346cm -1 The absorption peaks at are NH bending vibration and stretching vibration, respectively. In summary, it can be proved that KH550 has a good chemical reaction with the GF surface and formed a new chemical bond.
[0068] like Figure 2 (b) shows that the wave number is 2978 cm -1 and 2871cm -1 The absorption peaks are related to the stretching vibrations of hydrocarbons, especially in aliphatic compounds. These peaks may be caused by the presence of oil or other organic matter adsorbed by ESP. In addition, the wave number 1420 cm -1 Corresponding to the bending vibration of CH, 2978 cm -1 and 2871cm -1 The corresponding position is the stretching vibration of CH, with a wave number of 2511 cm -1 It is usually associated with the stretching vibration of SH or PH, which may be caused by trace amounts of sulfur or phosphorus compounds in ESP, and the wave number 1795 cm -1 It is usually associated with the stretching vibration of C=O, which may be caused by the ester group in a small amount of organic matter, 877cm -1 and 712cm -1 CO3 in CaCO3 2- ions, these wave numbers are typical of CaCO3, but it should be emphasized that the infrared spectra of ESP and ESPKH change very little, which may be the reason for the low concentration of KH550. Therefore, by further observing the Mapping image of ESPKH, we can find that ESP contains a large amount of Si elements, which proves that KH550 has been grafted onto ESP. The dispersion of inorganic fillers in the substrate is crucial to achieve the expected performance of the composite material. Therefore, the morphology, size and dispersion of ESP were studied by scanning electron microscopy. Figure 2 (d) It can be seen that the shape of ESP is close to a sphere with a diameter of about 0.2 μm, and 0.5 wt% ESP is distributed more evenly in the composite matrix.
[0069] Embodiment 3
[0070] Reference Figure 3, which is an embodiment of the present invention, a scanning electron microscope (ZEISS Sigma 300) was used to observe the microscopic morphology of the material. After the surface was gold-sprayed, all fracture sections were examined under vacuum conditions.
[0071] Figure 3 Scanning electron microscope (SEM) images of bending fracture sections of (a, a′) R-PE / HDPE, (b, b′) GF, (c, c′) MAH / GF, (d, d′) MAH / GFKH and (e, e1, e3) GFKH / ESPKH0.5; (e2) mapping image of GFKH / ESPKH0.5.
[0072] The changes in the properties of the composites can be elucidated by observing the interface morphology between R-PE / HDPE, GF, and ESP using scanning electron microscopy (SEM), e.g. Figure 3 (b) and 3(b'), it can be observed that the GF surface is smooth and has poor adhesion to R-PE / HDPE. When subjected to stress, GF can easily separate from the matrix and generate cracks and holes in the composite structure, thus affecting its ability to reinforce the material. However, Figure 3 As shown in (c), (c'), (d), and (d'), adding 5wt% PE-g-MAH into the composite system and modifying GF with silane coupling agent KH550 can enhance the compatibility of GF with R-PE / HDPE.
[0073] Figure 3 (e) is the SEM image of GFKH / ESPKH0.5, which shows that GFKH is uniformly dispersed throughout the R-PE / HDPE matrix, and when the composite is subjected to large forces, there are obviously no identifiable gaps and holes in the composite structure, which means that the adhesion between GFKH and R-PE / HDPE is strong enough to withstand external stress without causing serious damage or delamination. Uniformly distributed GFKH is crucial to improving mechanical properties. In addition, the absence of voids or gaps ensures an uninterrupted load transfer path and promotes effective stress distribution throughout the material.
[0074] The structure-activity relationship between ESPKH, GFKH and substrates can be effectively demonstrated by magnified observations at different positions, e.g. Figure 3 As shown in (e1), GFKH and R-PE / HDPE show a close interface combination, and the silver lines generated by the stress on the substrate surface are evenly distributed, indicating that the stress is well dispersed. Figure 3 In (e2), it can be clearly seen that ESPKH adheres to the surface of GFKH, increasing its roughness and the contact area with the substrate. Figure 3(e3) shows the SEM image of R-PE / HDPE under external force, showing many gaps and silver lines on the surface of the matrix, in which ESPKH is evenly dispersed in these gaps. Therefore, when subjected to external force, ESPKH plays a “bridge” connection role to absorb, transmit and disperse energy.
[0075] Embodiment 4
[0076] Reference Figure 4 , which is an embodiment of the present invention, the crystallization and melting properties of the sample are analyzed by using a TA DSC250 differential scanning calorimeter (DSC). Initially, the temperature of the sample is increased from 30°C to 200°C, and then kept warm for 10 minutes to eliminate the previous thermal effect. Subsequently, the sample is cooled back to 30°C and then heated to 200°C again. The whole process is carried out under N2 atmosphere, and the heating and cooling rates are both 10°C / min. The data of the cooling and second heating stages are recorded. Finally, the crystallinity can be calculated using the following formula:
[0077]
[0078] Where ΔHm is the melting enthalpy of the sample, W HDPE and W R-PE is the mass fraction of HDPE and R-PE in the composite material, and the enthalpy change of the complete crystallization process of HDPE and R-PE is ΔH HDPE and ΔH R-PE It indicates that the measured values are 286.7 J / g and 293.0 J / g respectively.
[0079] exist Figure 4 In the figure, (a) is a schematic diagram of the crystallization curve of R-PE / HDPE and its composites;
[0080] (b) is a schematic diagram of the melting curves of R-PE / HDPE and its composites;
[0081] (c) is a schematic diagram of the crystallization temperature and melting temperature of R-PE / HDPE and its composites;
[0082] (d) Schematic diagram of the crystallinity of R-PE / HDPE and its composites.
[0083] Figure 4 The effect of adding ESP and GF on the composite crystallization characteristics is shown, where the crystallization temperature and melting temperature of the composite are represented by Tc and Tm, respectively. Figure 4It can be seen that the melting temperature of R-PE / HDPE is 131.44℃ and the crystallization temperature is 115.93℃, which is not significantly different from other composites. The results show that the crystallinity of the composites is affected by GFKH and ESPKH. Specifically, we observed that the crystallinity of GFKH / ESPKH0.5 reached 62.9%, which was 33.3% higher than that of pure R-PE / HDPE. This enhancement in crystallinity can be attributed to the role of ESPKH as a nucleation site for crystal growth in the composite. Scanning electron microscopy also observed that the addition of compatibilizers and coupling agents had an effect on the crystallinity of the composites. It helps to mix the matrix and the reinforcement phase and reduce phase separation, thereby forming more nucleation sites. The introduction of these additional nucleation sites changes the movement of the molecular chains and increases the interaction between the matrices, thereby producing a steric effect. During the curing process, the presence of more nucleation sites promotes better arrangement between polymer chains, resulting in an increase in the overall crystalline area within the R-PE / HDPE matrix. The crystallinity of GFKH / ESPKH0.7 is slightly lower than that of GFKH / ESPKH0.5, which may be due to the agglomeration of ESPKH hindering the movement of the polymer chains, thereby reducing the crystallinity of the composite material.
[0084] Embodiment 5
[0085] Reference Figure 5 , which is an embodiment of the present invention, uses a Bruker AXSD8 X-ray diffractometer to detect the crystal structure of the composite material, with a scanning range of 5° to 80° and a scanning rate of 1° / min.
[0086] XRD patterns of R-PE / HDPE and its composites are shown in Figure 5 As shown, Figure 5 As shown in (a), the main characteristic peaks of R-PE / HDPE are at 2θ=21.7° and 24.0°, representing the crystal planes (110) and (200), respectively. In nature, the three crystal forms of calcium carbonate (CaCO3) are calcite, aragonite and quartz, among which calcite is the most stable. The chemical composition of eggshell is mainly composed of about 95% of CaCO3 in the form of calcite. Figure 5 (a) shows characteristic peaks at 2θ of 23.3° and 29.7°, among which a higher intensity peak was observed at 29.7°, indicating the presence of a crystalline mineral phase in the form of calcite, which represents the common polymorphic feature of CaCO3 in eggshell.
[0087] from Figure 5(c) It can be seen that the addition of GFKH and ESPKH has little effect on the position of the diffraction peaks of the R-PE / HDPE-based composites, indicating that the effects of these two additives on their crystal structure can be ignored. However, after adding GF, the intensity of the characteristic peaks of the R-PE / HDPE composites increased slightly due to the nucleation effect of the fiber-filled polymer composites during the molding process. NE Zafeiropoulos et al. recovered glass fibers from glass fiber reinforced polyethylene composites and mixed them with pure polyethylene. They found that the polymer residues and the new matrix can be recrystallized to form a transcrystalline layer around the fibers. In addition, as Figure 5 As shown in (d), when ESPKH is added, a new characteristic peak appears at 29.7° corresponding to the CaCO3 (110) crystal plane in the composite material. ESPKH enhances the intensity of the two main diffraction peaks, which indicates that it is both a promoter and a nucleating agent, which can accelerate the crystallization rate, improve the grain structure, and increase the stiffness of the product. These findings are consistent with the DSC results.
[0088] Embodiment 6
[0089] Reference Figure 6 , which is an embodiment of the present invention, the Vicat softening temperature (VST) test of the composite material was carried out according to ISO 306:2004, the sample size was 10mm×10mm×4mm, and the heating rate was 50°C / h.
[0090] In order to evaluate the heat resistance and mechanical properties of the materials in practical applications, we conducted Vicat softening point tests (VST) and mechanical tests on R-PE / HDPE and their composites. VST is an important indicator for characterizing the heat resistance of polymers. It can characterize the ability of polymers to maintain mechanical properties at a certain heating rate. Improving the VST of thermoplastics can increase their use temperature, such as Figure 6 As shown in (a), the incorporation of GFKH and ESPKH enhances the VST of the composite, while the addition of only 0.5wt% ESPKH has a negligible effect on VST, and the VST of the composite GFKH / ESPKH0.5 (115.7℃) is 6.9℃ higher than that of R-PE / HDPE (122.6℃). This is because GFKH and ESPKH can not only resist high temperatures, but also play the role of a hard skeleton in the matrix resin, and from the DSC data, it can be seen that GFKH and ESPKH enhance the crystallinity of the composite, resulting in the formation of a strong crystal network structure inside the material, thereby enhancing heat resistance.
[0091] Figure 6 (a) Vicat softening temperature (VST), (b) tensile strain-stress curve, (c) flexural strain-stress curve and (d) impact strength of R-PE / HDPE and its composites.
[0092] The experimental results of mechanical properties of R-PE / HDPE and its composite materials are shown in Figure 6 (bd) is shown in Table 2. Detailed experimental data are given. It is well known that the interfacial compatibility between PE and GF is very poor. Therefore, the addition of 30 wt% GF can only slightly improve the tensile strength and flexural strength of the composite material, while reducing the impact strength. However, the comparison between GF and MAH / GF shows that the addition of 5 wt% PE-g-MAH can effectively improve the overall mechanical properties of the composite material due to the coupling effect of PE-g-MAH: first, the anhydride groups of the side chains react chemically with the hydroxyl groups on the surface of GF to form hydrogen bonds; second, the PE chains from PE-g-MAH are entangled with the j substrate, which effectively enhances the compatibility between GF and the substrate.
[0093] Table 2 Mechanical properties of R-PE / HDPE and its composite materials
[0094]
[0095] After adding ESPKH, the mechanical properties of the composites are further improved. It is worth noting that the tensile strength, flexural strength and impact strength of GFKH / ESPKH0.5 are 125.3%, 115.3% and 79.8% higher than those of R-PE / HDPE, respectively. The changes in the mechanical properties are well confirmed by the changes in the SEM images and DSC data, such as the good interfacial bonding between GFKH and R-PE / HDPE; the bridging effect of ESPKH; ESP is a high-strength, large-surface-area inorganic filler that can be used as a rigid material to enhance the mechanical properties of composites, and can also be added to thermoplastic materials as a nucleating agent to improve their crystallinity.
[0096] To evaluate the performance and quality of the composites in this experiment, we compared our results with previously reported data.
[0097] Table 3: Data comparison of mechanical properties of different composite materials
[0098]
[0099]
[0100] Through the above comparison, it can be found that the addition of untreated GF and ESP alone cannot satisfactorily improve the mechanical properties of HDPE-based composites. HDPE, GF, PLA and PP are incompatible materials, and their melting and blending will lead to fluctuations in strength and toughness. In this study, GFKH, ESPKH and PE-g-MAH were added to HDPE / R-PE. Due to the synergistic effect of GF and ESP and the improved interfacial compatibility of KH550 and PE-g-MAH treatment, the tensile strength of the composite increased by 125.3%, the impact strength increased by 79.8%, and the flexural strength increased by 115.3%. The results show that GFKH / ESPKH0.5 has excellent mechanical properties.
[0101] Embodiment 7
[0102] Reference Figure 7 , which is an embodiment of the present invention, uses an XJD-50 electronic simply supported beam impact testing machine to carry out a notched impact test on the composite material. The bending and tensile test data of the composite material are measured on a Wanshang testing machine (ETM104B), and the crosshead speeds are 2mm / min and 50mm / min respectively. All mechanical property data are the average values of 5 test data.
[0103] Dynamic Mechanical Analysis (DMA) measures the mechanical properties of a material as a function of time, temperature or frequency. Figure 7 The loss modulus and storage modulus of R-PE / HDPE and its composites vary with temperature. Figure 7 It can be clearly seen that the incorporation of GFKH and ESPKH leads to the enhancement of the loss modulus and storage modulus of the composite material. The initial storage modulus (918.8MP) of sample GFKH / ESPKH0.5 is significantly increased by 107.9% compared with R-PE / HDPE (441.9MP), which can be attributed to the inherent stiffness of GF and ESP. At the interface of the composite material, GF and ESP partially relieve the stress, and their stiffness offsets the viscoelasticity of the R-PE / HDPE matrix. Silane coupling agents KH550 and PE-g-MAH further enhance the interfacial compatibility and stress transfer between the components. It is worth noting that the storage modulus of the composite material shows a gradual downward trend between 30°C and 130°C. This is because as the temperature increases, the thermal kinetic energy of the internal molecules of R-PE / HDPE increases, resulting in the movement and slippage of the chain segments and the gradual softening of the composite material. Therefore, the offset effect of GFKH and ESPKH weakens, resulting in a gradual decrease in the gap between the storage moduli of different composite materials.
[0104] The loss modulus of a polymer represents the energy lost due to viscous deformation when the material is deformed, e.g. Figure 7As shown in (b), in the temperature range of 30 to 60 °C, the addition of GFKH and ESPKH gradually increases the loss modulus of the composite material. This enhancement is due to the hindrance imposed by the rigid material on the R-PE / HDPE molecular chain segments, resulting in increased energy absorption during the movement of the molecular chain. The peak of the loss modulus appears at around 60 °C, which is mainly due to the α-relaxation in HDPE, which characterizes the molecular movement in its crystalline region. It can also be observed that the incorporation of GFKH and ESPKH into the R-PE / HDPE composite causes the peak temperature to shift to a higher temperature. This shift can be attributed to the formation of interfaces between different materials, resulting in increased energy consumption during the transfer of polymer molecular chains.
[0105] Embodiment 8
[0106] Reference Figure 8 , which is an embodiment of the present invention, the dynamic mechanical properties of the composite material in the range of 30 to 130° C. were tested using DMA (PerkinElmer 8000), the heating rate was 5° C. / min, and the test frequency was 1 Hz.
[0107] Thermogravimetric (TG) and differential thermogravimetric (DTG) curves of composite materials with different components in nitrogen atmosphere are shown in Figure 2. Figure 8 As shown in the figure, the temperature at which the mass loss reaches 5% is represented by T5%. Figure 8 It can be seen that the addition of GF, KH550 and ESP has an improved effect on the heat resistance of the composite material, such as reducing the maximum weight loss rate of the composite material and increasing the T5% of the composite material. 5% (415.6℃) than R-PE / HDPE 5% (374.6℃) increased by 41℃. However, the presence of PE-g-MAH had an adverse effect on the thermal stability.
[0108] The above phenomenon is explained as follows: (1) The addition of GF reduces the proportion of R-PE / HDPE in the composite material. At the same time, due to its rigid nature, it also restricts the movement of R-PE / HDPE molecular chains. In addition, the "tortuous path" effect of GF enhances thermal stability and delays the escape of volatile products and the formation of char during thermal degradation;
[0109] (2) The rapid thermal oxidative degradation of the composites was attributed to the formation of carboxylic acid groups during the decomposition of MAH and the potential peroxide groups used to graft MAH onto PE, which accelerated the decomposition of PE. The fiber and fiber-matrix interface can significantly change the oxygen transport characteristics. Free radicals introduced by the fiber, matrix or coupling agent may exist at the interface of the composites, which are easy to react with the diffusion of oxygen and accelerate the decomposition.
[0110] (3) KH550 changes the interface structure of each component in the composite material. The introduced coupling groups can serve as the bridging structure of the cross-linked fibers. The addition of KH550 reduces the number of cross-linking points between PE-g-MAH and GF, and introduces Si elements into the R-PE / HDPE molecular chain.
[0111] (4) The unique structure of ESP determines its special physical and chemical properties. Coupled with the high bond energy of CaCO3, as an inorganic phase, it improves the thermal stability of the system. In addition, the rigidity of CaCO3 limits the movement of R-PE / HDPE molecular chains, thereby improving the heat resistance of the composite material. In addition, KH550 enhances the interfacial adhesion between ESP and the matrix, increases the roughness and viscosity inside and on the surface of the composite material, complicates the heat transfer path of the material during the melting process, and further improves the heat resistance of the composite material.
[0112] Embodiment 9
[0113] Reference Fig. 9 , which is an embodiment of the present invention, a thermal analyzer is used to analyze the composite material, and the sample is heated from 30° C. to 800° C. at a rate of 10° C. / min.
[0114] Fig. 9 The schematic diagram illustrates the mechanism of molecular interaction and polymer chain movement to clarify the microstructure formed at the interface in GF, ESP and R-PE / HDPE composites. First, KH550 undergoes a hydrolysis process to form Si-OH bonds, which subsequently react with -OH on the GF surface to form Si-O-Si bonds. The other end of the silane coupling agent has good compatibility with polyethylene, allowing molecular entanglement between the carbon chain of polyethylene and part of the molecular chain of the silane coupling agent, thereby playing a connecting role. Another thing worth noting is that when the resin is melted, the PE-g-MAH chain with a lower molecular weight first moves to the GF surface due to its shorter relaxation time and faster diffusion compared to the long chain. Subsequently, the C=O bond on PE-g-MAH reacts with -OH on the GF surface to form Si-OC bonds. At the same time, the short chain segment of PE-g-MAH entangles with the long chain segment of the substrate and drives its movement by diffusion. Finally, R-PE / HDPE is firmly bonded to the GF surface. Therefore, when subjected to pressure, the adhesion between GF and R-PE / HDPE is difficult to release.
[0115] The incorporation of ESP in the composites produces several significant enhancements. First, it adheres to the GF surface, increasing its roughness and thus the contact area with the substrate. This increased contact area promotes good adhesion between the GF and the substrate, thereby improving the mechanical properties. Second, since ESPKK is evenly distributed inside the substrate, it plays a key role in absorbing, transferring and dispersing energy when subjected to external forces. It uniformly fills the cracks and silver lines throughout the composite, acting as a bridge connecting the different components. This bridging effect effectively blocks crack propagation by evenly distributing stress in various regions of the composite. A comprehensive understanding of polymer chain diffusion and the interaction between GF and ESP is crucial to understanding the interface formation mechanism of these composites. The interface not only determines their mechanical properties but also plays an integral role in their ability to withstand high temperatures.
[0116] The invention adopts a certain proportion of glass fiber (GF) and eggshell powder (ESP) to prepare a recycled polyethylene / high-density polyethylene (R-PE / HDPE)-based composite material to improve the heat resistance and mechanical properties of the composite material. The significant improvement of the mechanical properties and heat resistance of the composite material is mainly attributed to the fact that the silane coupling agent KH550 and polyethylene grafted maleic anhydride (PE-g-MAH) enhance the interface adhesion of the composite material, and the synergistic effect of ESP and GF: the ESP is partially dispersed in the R-PE / HDPE and partially attached to the GF, and the chain effect between them enables the stress to be well absorbed, transmitted and dispersed. The GF and ESP serve as reinforcing agents and nucleating agents, improve the mechanical properties and crystallization properties of the composite material, reduce the ratio of R-PE / HDPE, increase the roughness and viscosity of the composite material, and complicate the transmission path of the melt fluid.
[0117] Through the above-mentioned multiple groups of experiments, the results show that the composite material containing 5wt% PE-g-MAH, 30wt% GFKH and 0.5wt% ESPKH has excellent mechanical properties, good thermal stability and high crystallization performance. Compared with R-PE / HDPE, the crystallinity, storage modulus, tensile strength, flexural strength and impact strength of GFKH / ESPKH0.5 composite material are increased by 33.3%, 107.9%, 125.3%, 115.3% and 79.8%, respectively. Thermal analysis shows that the Vicat softening temperature (VST) and 5% weight loss temperature (T 5%) were increased by 6.9℃ and 41℃ respectively. The present invention mainly studies the relationship between the heat resistance, mechanical properties and microstructure of the composite material, which will provide new ideas for the modification of recycled thermoplastic resins and the structural design of high-performance composite materials. The test results were compared with those of traditional building materials, and it was found that the GFKH / ESPKH0.5 composite material has great potential for application in sustainable building components, parts and products (such as sign boards, corrugated pipes, partitions, cover boards, lightweight roof panels, door and window frames), etc.
[0118] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A reinforced recycled polyethylene and high-density polyethylene composite material, characterized in that: The composite material comprises: Recycled polyethylene, high-density polyethylene, polyethylene grafted with maleic anhydride, glass fiber treated with KH550, and eggshell powder treated with KH550 after constant temperature drying; Among them, the mass proportion of recycled polyethylene is 32.25%; High-density polyethylene accounts for 32.25% by mass; A certain proportion of polyethylene grafted with maleic anhydride, glass fiber treated with KH550, and eggshell powder treated with KH550; The recycled polyethylene, high-density polyethylene, polyethylene grafted with maleic anhydride, glass fiber treated with KH550 and eggshell powder treated with KH550 are fully mixed, and the mixed materials are melted, extruded and granulated to obtain the composite material.
2. The reinforced recycled polyethylene and high-density polyethylene composite material according to claim 1, characterized in that: The glass fiber treated with KH550 refers to the glass fiber treated with a KH550 mixed solution with a mass concentration of 1.0%, and the eggshell powder treated with KH550 refers to the eggshell powder treated with a KH550 mixed solution with a mass concentration of 1.0%.
3. The reinforced recycled polyethylene and high-density polyethylene composite material according to claim 2, characterized in that: The KH550 mixed solution with a mass concentration of 1.0% is prepared by adding silane coupling agent KH550 to a solution with a mass ratio of distilled water to ethanol of 1:
1.
4. The reinforced recycled polyethylene and high-density polyethylene composite material according to claim 1, characterized in that: The constant temperature is 80° C. and the drying time is 8 hours.
5. The reinforced recycled polyethylene and high-density polyethylene composite material according to claim 1, characterized in that: The recycled polyethylene, high-density polyethylene, polyethylene grafted with maleic anhydride, glass fiber treated with KH550 and eggshell powder treated with KH550 are melted, extruded and granulated within a temperature range of 175° C. to 180° C., and the produced granules are dried at 80° C. for 8 hours.
6. The reinforced recycled polyethylene and high-density polyethylene composite material according to claim 1, characterized in that: The polyethylene grafted with maleic anhydride accounts for 5% by weight, and the glass fiber is modified with silane coupling agent KH550 to enhance the compatibility of the glass fiber with recycled polyethylene / high-density polyethylene.
7. The reinforced recycled polyethylene and high-density polyethylene composite material according to claim 1, characterized in that: The mass proportions of the glass fiber treated with KH550 and the eggshell powder treated with KH550 are 30% and 0.5% respectively, so that a strong crystal network structure is formed inside the material, the crystallinity of the composite material is enhanced, and thus the heat resistance is enhanced.
8. The reinforced recycled polyethylene and high-density polyethylene composite material according to claim 1, characterized in that: The incorporation of 30% of the glass fiber treated with KH550 and 0.5% of the eggshell powder treated with KH550 enhances the loss modulus and storage modulus of the composite material.
9. The reinforced recycled polyethylene and high-density polyethylene composite material according to claim 2, characterized in that: KH550 with a mass concentration of 1.0% enhances the interfacial adhesion between the eggshell powder and the matrix, increases the roughness and viscosity inside and on the surface of the composite material, complicates the heat transfer path of the material during the melting process, and improves the heat resistance of the composite material.
10. A method for preparing a composite material of reinforced recycled polyethylene and high-density polyethylene, characterized in that: The preparation method is applicable to any one of the composite materials in claims 1 to 9 above, and the preparation method comprises the following steps: S1: Material drying: Recycled polyethylene, high-density polyethylene, glass fiber treated with KH550, polyethylene grafted with maleic anhydride and eggshell powder treated with KH550 were dried at a constant temperature of 80°C for 8 hours; S2: adding silane coupling agent KH550 to a solution with a mass ratio of distilled water to ethanol of 1:1 to prepare a mixed solution with a mass concentration of 1.0% KH550, and after ultrasonic treatment of the mixed solution for 1 hour, the dried glass fiber and eggshell powder were respectively immersed in an appropriate amount of the mixed solution for 2 hours, and then the treated materials were transferred to an oven at 80°C for 4 hours; S3: The components of the composite material are fully mixed, and the uniformly mixed materials are melted, extruded and granulated at a temperature range of 175° C. to 180° C., and the granules are dried at 80° C. for 8 hours.